Relationships Between Three Eating Behaviors and Nine Motives for Food Choices Among Brazilian Adults: A Structural Equation Model - Silva, Wanderson Roberto da. [UNESP]; Ferreira, Eric B.; Marôco, João; da Silva Júnior, Sinézio I.; Teodoro, Micaela A.; Campos, Juliana A. D. B. [UNESP] (SAGE Publications, 2023)
We examined the relationships between three eating behaviors and nine motives underlying food choices made by Brazilian adults. Using participant responses to the short version of the Three-Factor Eating Questionnaire and the Food Choice Questionnaire, we investigated eating behaviors (cognitive restriction, uncontrolled eating, and emotional eating) and motives for food choices (health, mood, convenience, sensory appeal, natural content, price, weight control, familiarity, and ethical concern). We used a structural equation model to test relationship pathways (β), with eating behaviors as independent variables and motives for food choices as dependent variables. Participants were 1297 individuals (69.5% female) with a mean age of 25.0 years (SD = 5.8). We confirmed the validity and reliability of the questionnaires in this sample. Restrictive eating behavior was significantly related to motives of health (β =.415), mood (β =.127), natural content (β =.364), weight control (β =.681), and ethical concern (β =.161). Emotional eating behavior was related to motives of mood (β =.277), health (β = −.137), and natural content (β = −.136). Uncontrolled eating behavior was related to motives of convenience (β =.226), sensory appeal (β =.121), price (β =.153), and familiarity (β =.090). We believe these findings can now help design future research and clinical interventions for managing people’s risky eating behaviors and promoting beneficial food choices.
Keywords: adults; Brazil; cognitive restriction; eating behavior; emotional eating; food choice; motives; questionnaire; structural equation modeling; uncontrolled eating